Estado del arte de los modelos quimiométricos para predicción de propiedades fisicoquímicas del turbo combustible (2017)
Jet fuel is traditionally analyzed under standards defined by the American Society for Testing and Materials (ASTM), which requires trained personal, infrastructure, specialized equipment and much more time than the one allowed to have industrial processes under control and plant adjustments . The advances in computational techniques applied in chemometrics have turned it into a valuable tool that complements conventional analytical chemistry due to its precision and ability to give fast reliable results. Under that frame this research on the state of the art of chemometrics applied in the prediction of jet fuel properties was done on official databases and web pages. The most studied properties are the distillation curve, API gravity, density, flash point, freeze point, viscosity and aromatic content. The majority of researches done so far include spectroscopic techniques such as infrared to elaborate the prediction models, although RAMAN and gas chromatography are also found. After summarizing and analyzing all de data from the research, it was determined that the best results are obtained using FTIR as spectra’s source along with PLS as correlation method.